Burden and types of support for family caregivers serving patients with chronic disease - Campos de Aldana, María Stella; Durán Niño, Erika Yurley; Rivera Carvajal, Raquel; Páez Esteban, Astrid Nathalia; Carrillo Gonzales, Gloria Mabel (Revista Cuidarte, 2019)
Introduction: An increase in chronic noncommunicable disease has been evidenced worldwide in this century; patients present with longer-lasting and more complex pathologies, generating dependence, requiring a caregiver at home; while different skills are required to improve care competencies. Objective: To identify types of support used by the family caregivers of patients with chronic noncommunicable disease and their relation with the caregivers’ burden. Materials and Methods: Quantitative-approach, cross-sectional and analytical study, applying these tools: "Characterization of the patient-caregiver dyad and Caregiver’s Zarit Burden Interview". The population comprised 62 dyads. OR were calculated in logistic regression. Results: 19.35% (12) of caregivers showed an intense level of burden, 20.97% (13) showed a light burden, and 59.68% (37) had no burden. Caregivers with intense burden state there is 0% of psychological and social support. The relevant variables in the burden level were daily hours of care OR = 1.14 (CI 95%: 1.01; 1.33), the higher the level of knowledge of the computer, the lower the possibility of increase in the level of burden with raw OR= 0.14 (CI95%: 0.02; 0.91), and adjusted OR = 0.07 (CI 95%: 0.007; 0.68).  Discussion: It is critical to continue investigating aspects that will reduce the caregivers’ burden, keep them healthy and under appropriate conditions to perform their role. Conclusions: It is necessary to strengthen the different types of support for family caregivers to reduce the burden level related to their work.
Keywords: Patients; Caregivers; Chronic Disease; Social Support